The Impact of Corruption on Economic Development and Community Welfare from Local And National Perspectives - Rudiyansah, Muhammad Mas Davit Herman; Rezki, Moch. Gufron Fajar (Abdurrauf Social Science, 2025)
Corruption is a fundamental problem that hinders development and undermines state legitimacy. In Indonesia, corrupt practices not only result in financial losses to the state but also have systemic effects that undermine governance, hinder economic growth, and exacerbate social inequality. This study aims to analyze in depth how corruption impacts economic development and public welfare, emphasizing its link to public access to basic services such as education, health, and infrastructure. The method used is a qualitative descriptive approach with a literature review approach, examining secondary data from academic journals, anti-corruption agency reports, investigative news, and public policy documents. The study results show that corruption creates market distortions, weakens national competitiveness, and diverts development funds to the interests of political and bureaucratic elites. This condition results in unequal distribution of development between regions, low quality public services, and weakened public participation in the development process. Furthermore, corrupt practices have an impact on declining public trust in state institutions, which in turn has the potential to lead to social instability and a crisis of government legitimacy. This research emphasizes that eradicating corruption requires a multidimensional strategy, ranging from consistent law enforcement and bureaucratic reform to the application of digital technology to increase transparency and accountability. Therefore, the findings of this study are expected to provide conceptual and practical contributions to formulating a more comprehensive, sustainable anti-corruption strategy that adheres to the principles of social justice for the realization of inclusive national development.  Abstrak: Korupsi merupakan salah satu masalah fundamental yang menghambat proses pembangunan dan melemahkan legitimasi negara. Di Indonesia, praktik korupsi tidak hanya berdampak pada kerugian finansial negara, tetapi juga menimbulkan efek sistemik yang merusak tata kelola pemerintahan, menghambat pertumbuhan ekonomi, serta memperparah kesenjangan sosial. Penelitian ini bertujuan untuk menganalisis secara mendalam bagaimana korupsi memengaruhi pembangunan ekonomi dan kesejahteraan masyarakat, dengan menekankan keterkaitannya terhadap akses publik pada layanan dasar seperti pendidikan, kesehatan, dan infrastruktur. Metode yang digunakan adalah kualitatif deskriptif dengan pendekatan studi literatur, yang mengkaji data sekunder dari jurnal akademik, laporan lembaga antikorupsi, berita investigatif, serta dokumen kebijakan publik. Hasil kajian menunjukkan bahwa korupsi menciptakan distorsi pasar, memperlemah daya saing nasional, serta mengalihkan anggaran pembangunan ke kepentingan elit politik dan birokrasi. Kondisi ini mengakibatkan ketimpangan distribusi pembangunan antarwilayah, rendahnya kualitas layanan publik, dan melemahnya partisipasi masyarakat dalam proses pembangunan. Selain itu, praktik korupsi berdampak pada menurunnya kepercayaan masyarakat terhadap institusi negara, yang pada gilirannya berpotensi menimbulkan instabilitas sosial dan krisis legitimasi pemerintahan. Penelitian ini menekankan bahwa pemberantasan korupsi memerlukan strategi multidimensi, mulai dari penegakan hukum yang konsisten, reformasi birokrasi, hingga penerapan teknologi digital untuk meningkatkan transparansi dan akuntabilitas. Dengan demikian, temuan penelitian ini diharapkan dapat memberikan kontribusi konseptual dan praktis dalam merumuskan strategi pemberantasan korupsi yang lebih komprehensif, berkelanjutan, serta berpihak pada prinsip keadilan sosial demi terwujudnya pembangunan nasional yang inklusif.